The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia - Williams, Kevin A.; Lelej, Arkady S.; Okayasu, Juriya; Borkent, Christopher J.; Malee, Rufeah; Thoawan, Kodeeyah; Thaochan, Narit (Zootaxa, 2019)
A review of female mutillids in southern Thailand is presented, based on literature, loaned material, and two field expeditions. Thirty-three species in 23 genera have been previously recorded from Thailand (Lelej 2005; Lelej et al. 2016, 2017; Okayasu et al. 2018). In March and April 2017, 337 female specimens were collected in the provinces of Krabi, Nakhon Si Thammarat, Phatthalung, Songkhla, and Trang. In May 2018, 255 female specimens were collected in the provinces of Kanchanaburi, Phetchaburi, and Surat Thani. These collected specimens were sorted into 38 morphospecies: 13 already known from Thailand, nine previously described species newly recorded from Thailand, and 16 new to science and described here. Based on loaned material, three more described species were newly recorded from southern Thailand and one more undescribed species was found. Keys to females of the 31 mutillid genera found in southeast Asia and 42 mutillid species studied from southern Thailand are provided. Illustrations and diagnoses are provided for each species studied in southern Thailand, including the following 17 new species: Bischoffitilla tokay Williams, Bischoffitilla cambrai Williams, Mickelomyrme puttasoki Williams, Mickelomyrme kinguri Williams, Nordeniella maleeae Williams, Smicromyrme helarctos Williams, Smicromyrme borkenti Williams, Smicromyrme thaochani Williams, Krombeinidia agricola Williams, Krombeinidia chang Williams, Krombeinidia baanmaka Williams, Orientidia manleyi Williams, Orientidia thoawanae Williams, Petersenidia modkhong Williams, Petersenidia leleji Williams, Trogaspidia pittsi Williams, and Trogaspidia wilsoni Williams. Three new synonyms and one new combination are recognized: Bischoffitilla lamellata (Mickel, 1933) = Squamulotilla arundinacea Pagden, 1934, syn. nov., Mickelomyrme pusillaeformis (Hammer, 1962), comb. nov. = Mickelomyrme yunnanensis Lelej, 1996, syn. nov., Trogaspidia pagdeni (Mickel, 1933) = Timulla (Trogaspidia) pagdeni nodoa Mickel, 1933, syn. nov. Finally, two other taxa are raised to full species from subspecies status, Eotrogaspidia oryzae (Pagden, 1934), status resurr., and Trogaspidia lingnani (Mickel, 1933), status nov. New combination is also proposed for Krombeinidia meeungensis (Cockerell, 1928), comb. nov. Twenty-three new country records are presented: 12 from Thailand, four from Vietnam, four from Laos, two from Cambodia, and one from Indonesia.